Chapter Canals, Cities, Museums, Libraries & Photography: a Reconnaissance Study of Regent's Canal, London - Diprose, Graham (Proceedings e report, 2018)
City waterways are a valuable part of our cultural heritage. Over the years the usage has changed from business to pleasure. Regent's Canal, cutting across north central London since 1820, has a rich social and industrial history. Much of this history has been and is being captured via photographs. Many of these are being lost due to limited museum resources and disparate collections. This paper reports on phase one of a fifteen-month exploratory research project. The research aims to explore ways of aiding image capture, selection, storage and retrieval. We hope to link with researchers elsewhere, especially in Italy.